Ultraviolet-B radiation exposure lowers the antioxidant capacity in the Arabidopsis thaliana pdx1.3-1 mutant and leads to glucosinolate biosynthesis alteration in both wild type and mutant. Issue 2 (21st January 2020) - Neugart, Susanne; Hideg, Éva; Czégény, Gyula; Schreiner, Monika; Strid, Åke
Abstract : We show the important and dual role of VitB6 as both an antioxidant and an enzymatic co-factor in Arabidopsis plants under exposure to supplementary UV radiation. Abstract : Pyridoxine (vitamin B6 ) and its vitamers are used by living organisms both as enzymatic cofactors and as antioxidants. We used Arabidopsis pyridoxine biosynthesis mutant pdx1.3-1 to study the involvement of the PLP-synthase main polypeptide PDX1 in plant responses to ultraviolet radiation of two different qualities, one containing primarily UV-A (315–400 nm) and the other containing both UV-A and UV-B (280–315 nm). The antioxidant capacity and the flavonoid and glucosinolate (GS) profiles were examined. As an indicator of stress, F v / F m of photosystem II reaction centers was used. In pdx1.3-1, UV-A + B exposure led to a significant 5% decrease in F v / F m on the last day (day 15), indicating mild stress at this time point. The antioxidant capacity of Col-0 wildtype increased significantly (50–73%) after 1 and 3 days of UV-A + B. Instead, in pdx1.3-1, the antioxidant capacity significantly decreased by 44–52% over the same time period, proving the importance of a full complement of functional PDX1 genes for the detoxification of reactive oxygen species. There were no significant changes in the flavonoid glycoside profile under any light condition. However, the GS profile was significantly altered, both with respect to Arabidopsis accession and exposure to UV. The difference in flavonoid and GS profiles reflects that the GS biosynthesis pathway contains at least one pyridoxine-dependent enzyme, whereas no such enzyme is used in flavonoid biosynthesis. Also, there was strong correlation between the antioxidant capacity and the content of some GS compounds. Our results show that vitamin B6 vitamers, functioning both as antioxidants and co-factors, are of importance for the physiological fitness of plants.